Educação e tecnologias práticas em cenários disruptivos - Sant'Anna, Daniel Vieira (Editora Oficina Universitária, 2022)
Far beyond theoretical and methodological aspects, the pandemic time has revealed the importance of technological artifacts, most of the time, conceived only as tools for instant communication or simple entertainment. Watching the low results of external evaluations and, mainly, the devaluation of our place of speech as educators, we still seek, with determination, the conduction of pedagogical practices that involve teachers and students, in a meaningful process. Thus, gathering these texts, fruits of research, experiences and intense studies of some educators, students of the Graduate Program in Education at UNESP, Campus de Marília, is synonymous with recognition and concreteness that education, as a social instrument, reflects the needs as well as the demands of an unprecedented time.